Effects of xanthan gum, konjac glucomannan, and arabinogalactan on the in vitro digestion and fermentation characteristics of biscuits - Liu, Fangwei; Chen, Suming; Dong, Dejun; Zhang, Yanli; Zhang, Shanshan; Pan, Yuhui; Ji, Haihua; Zhang, Ziyi; Huang, Xinru; Zhang, Lin; Liu, Huan; Hu, Jielun (Food & function, 2023)
Background : Diabetes and its complications have a significant economic impact on individuals and their families. A diet with a low glycemic index (GI) and high fiber content is considered to be associated with the control of blood glucose. Scope and approach : This study explored the effect of polysaccharides, i.e. , xanthan gum (BXG), konjac glucomannan (BKG), and arabinogalactan (BAG), on the digestive and prebiotic characteristics of biscuits using a simulated digestion and fermentation model in vitro . Also, the rheological property and structural properties of the polysaccharides were measured to clarify their structure–activity relationships. Key findings and conclusions : During simulated gastrointestinal digestion, the results showed that three types of biscuits containing polysaccharides were low GI foods (estimated GI < 55), in which BAG had the lowest estimated GI value. During in vitro fermentation with diabetic or healthy subjects’ fecal microbiota, the three types of biscuits containing polysaccharides (after digestion) decreased the fermentation pH, increased the level of short-chain fatty acids, and modulated the microbiota composition over time. Among the three types of biscuits, BAG increased the abundance of Bifidobacterium and Lactobacillus during fermentation in diabetic and healthy subjects’ fecal microbiota. These results showed that the addition of a lower-viscosity polysaccharide (arabinogalactan) may be more beneficial for the blood glucose control of biscuits.